2017
DOI: 10.1080/23311975.2017.1301195
|View full text |Cite
|
Sign up to set email alerts
|

Assessing service quality of online bill payment system using extended SERVQUAL model (SERVQUAL-Butterfly model): A case study of Dhaka electric supply company limited (DESCO), Bangladesh

Abstract: The aim of this paper is to assess the service quality of Dhaka Electric Supply Company Limited's (DESCO) online bill payment system using extended SERVQUAL model termed as SERVQUAL-Butterfly Model that integrates customer expectation and perception of actual service quality, customer satisfaction, and loyalty. Using random sampling method, primary data were collected from a total of 300 customers from three operating zones of DESCO. The data were analyzed through PLS-SEM second-order hierarchical modeling app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
2
11
0
1
Order By: Relevance
“…, 2008). To assess the validity of the reflective constructs, we performed convergent validity tests for the construct by checking the measurement items loaded with significant t-stat and p -values (Lowry and Gaskin, 2014; Rahman et al. , 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2008). To assess the validity of the reflective constructs, we performed convergent validity tests for the construct by checking the measurement items loaded with significant t-stat and p -values (Lowry and Gaskin, 2014; Rahman et al. , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…We also assess internal reliability of the reflective constructs using the Cronbach's alpha to test item's reliability and composite reliability tests to assess the construct's reliability (Hoque, 2016; Hair et al. , 2013; Rahman et al. , 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kemampuan perusahaan dalam memberikan pelayanan kepada pelanggan menjadi salah satu factor yang menentukan keberhasilan kualitas perusahaan itu sendiri menurut (Lupiyoadi, 2001). Salah satu indicator pendekatan kualitas jasa yang biasa banyak dijadikan bahan acuan dalam riset pemasaran adalah model SERVQUAL (service quality) yang dikembangkan oleh Parasuraman dikutip oleh (Rahman et al, 2017) yaitu: bukti fisik (tangible), keandalan (reliability), daya tanggap (responsiveness), jaminan (assurance), dan empati (empathy). Model ini digunakan untuk mengerti lebih dalam harapan atau persepsi pelanggan terhadap pelayanan yang diinginkan, yang dapat digunakan dalam menghasilkan peningkatan kualitas pelayanan.…”
Section: Pendahuluanunclassified
“…Functional quality dimensions have been identified in previous studies focussed on the measurement of users' perceptions of service delivery (Brady and Cronin, 2001; Elnaghi et al , 2018; Rahman et al , 2017; Santos, 2003). In this study, the primary dimensions of functional quality were identified by synthesising the literature studies and evaluating users' perceptions of functional quality (interactivity, responsivity and serviceability) using mobile and electronic platforms.…”
Section: Literature Reviewmentioning
confidence: 99%